Blind Justice: What does that mean? - Munro, William (2016)
First paragraph: DURING the early Renaissance a number of engravings produced outside of Italy (Dürer (1498) and Bruegel (1561-62)) represented allegories of Justice that offered a very different reading from the later and more familiar Enlightenment interpretations of Justice. What was distinctive about these engravings was the appearance of Justice wearing a blindfold. However, instead of symbolising the impartiality of Justice, as the blindfold commonly does from the C17 onwards, these engravings represent Justice as being blind to its own origins in legal deception and arbitrary violence. Not only in these engravings is Justice made blind to its obscene and violent origins but, it may be interpreted, that these negative attributes are also hidden from us. We are in a sense blind to them